ANALISIS PERBANDINGAN BIAYA DAN WAKTU PELAKSANAAN BETON HALF SLAB DENGAN BETON KONVENSIONAL PADA PROYEK REVITALISASI MUSEUM MANDALA MATHIKA SUBAK - Landuh, Ni Putu Desi Sukamdani; Triswandana, I Wayan Gde Erick; Eryani, I Gusti Agung Putu (Jurnal Ilmiah MITSU (Media Informasi Teknik Sipil Universitas Wiraraja), 2025)
The construction implementation system in the Mandala Mathika Subak Museum Revitalization project uses the cast in situ or conventional method including floor slab work. The implementation of floor slab work with the cast in situ method requires a long processing time and a lot of labor and costs incurred. In the construction of the building, the selection of work methods is very influential on the implementation time and cost. The selection of the right method will make the development efficient. One of them is the use of precast concrete such as half slab. In this study will compare conventional methods and half slab methods from the aspects of implementation time and cost, which is more profitable. The results of the comparative analysis of execution time and costs from the calculation of cast-in-situ and half-slab plates in the Revitalization Project of the Mandala Mathika Subak Museum show that using the half-slab method saves 33% in costs compared to the cast-in-situ method, with a cost difference of Rp. 552,730,037, and can accelerate the execution time of 43% or 19 days.